2019
DOI: 10.1155/2019/9454580
|View full text |Cite
|
Sign up to set email alerts
|

Is Migraine an MPV-Related Disease? An Observational Study of Polish Neurological Patients

Abstract: Many studies have found correlations between abnormal MPV and clinical reactivity in a variety of diseases. In the present paper, we sought MPV-related neurological diseases that are less frequently reported in the literature. The electronic medical records of 852 neurological patients with mean platelet volume (MPV) measurements (F = 45%, age = 55.7 ± 18.7, 8–104) were searched after the patients had received a diagnosis of a neurological disease (new and old episodes) according to the nine classes of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[ 23 ] Although the mechanism between the migraine and stroke was not fully identified, some data propose that changes in platelet functions could have a role in patients with migraine, especially in relation to aura and its effect on stroke and vascular events. [ 26 27 ] White matter hyperintensities are considered to be asymptomatic in early stages in patients, but with progression, they can have a role in the development of cerebrovascular and neurodegenerative diseases. [ 28 ] There are multiple theories suggested for the mechanism of WMH, but the major cause and pathophysiology are still undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Although the mechanism between the migraine and stroke was not fully identified, some data propose that changes in platelet functions could have a role in patients with migraine, especially in relation to aura and its effect on stroke and vascular events. [ 26 27 ] White matter hyperintensities are considered to be asymptomatic in early stages in patients, but with progression, they can have a role in the development of cerebrovascular and neurodegenerative diseases. [ 28 ] There are multiple theories suggested for the mechanism of WMH, but the major cause and pathophysiology are still undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the large mean platelet volume (MPV) contained 5-hydroxytryptamine (5-HT) in their dense granule, representing the activity of platelet, associated with prothrombotic and migraine headache [31]. Migraine is considered an independent risk factor for vascular dysfunction in central nervous system, especially in the young to mid-aged women.…”
Section: Hypercoagulability and Inflammationmentioning
confidence: 99%
“…Treatment principles of headache include rescue approach, change lifestyle, nonpharmacologic or pharmacologic migraine prophylaxis, and combination therapeutics. The patients are highly encouraged to get advice from physicians on how to change lifestyle to control migraine attacks, such as to avoid trigger, sleep better, improve eating habit, do exercise and maintain relax [31,[80][81][82]. Prophylaxis medications, e.g., venlafaxine, propranolol, topiramate, valproid acid, lamotrigine, and acetazolamide have been tried.…”
Section: Abortive and Prophylactic Treatment Of Migrainementioning
confidence: 99%
“…Due to the association with neurogenic inflammation, studies have been performed investigating whether there is a correlation between migraine and hemogram parameters. Some studies have identified significant correlations between migraine and MPV, while others have not [5,6]. The common denominator of these studies is that they have generally been performed in adult patients.…”
Section: Introductionmentioning
confidence: 99%